Physical Demands in Elite Futsal Referees During Spanish Futsal Cup - Serrano, Carlos; Sánchez-Sánchez, Javier; Felipe, Jose Luis; Hernando, Enrique; Gallardo, Leonor; Garcia-Unanue, Jorge (Frontiers in Psychology, 2021)
In futsal there are two referees on the playing court and their capacity to respond to physical and physiological demands imposed during the game is essential for the success. The futsal characteristics such as size pitch, referees position and rules of games or type of league could impose specific physical efforts probably. The aim of this study were to analyze the physical demands of eight elite referees (age 40 ± 3.43 years; height 1.80 ± 0.03 m; weight 72.84 ± 4.01 kg) from seven matches of Spanish Futsal Cup 2020. The physical activity of each referee during the match was monitored with a Local Positioning System, which was installed on futsal pitch where the matches were played. The data differences were evaluated as Paired-Samples T-Test procedure. The results revealed a similar total distance between halves (2888.39 m vs 2831.51 m). The zone 3 distance (15.1-18 km·h-1) showed a significative decrease (p < 0.05) during the match in comparison to the first and second halves (-24.48 m; CI95%: -9.54 to -39.42; ES: 0.56). The number of high-intensity acceleration (-10.29; CI95%; 3.71 to 16.86; ES: 0.91) and deceleration (-24.86; CI95%; 11.59 to 38.12; ES: 0.99) decreased in the second half of the match (p < 0.05). Therefore, the use of the tracking device to monitoring physical performance provides knowledge of the specific activity profile from futsal referees. This information to can be useful to design more accurate the training programs.